Prevalence of insulin resistance in obese adolescents - Aman B. Pulungan; Ardita Puspitadewi; Rini Sekartini (Indonesian Pediatric Society, 2013)
Background Childhood obesity is a global health problem, withthe prevalence is differed in each country and affected by manyfactors, such as lifestyle and physical activity. Insulin resistance(IR) as a basic mechanism of several metabolic diseases in obesity,is related with metabolic syndrome (MetS) along with its longterm complications, such as type 2 diabetes mellitus (T2DM).Several factors are known to be associated with IR, and thepresence of acanthosis nigricans (AN) has an important meaningin predicting IR.Objectives To assess the prevalence of IR, MetS in obeseadolescents and its potentially associated factors, such as gender,signs of AN, and family history of metabolic diseases.Methods A cross-sectional study was performed in obeseadolescents, aged 12-15 years, over a two-month period. Fastingblood glucose, insulin, and lipid profiles were measured. Obesitywas defined using body mass index (BMI). Insulin resistancewas quantified by the homeostasis model assessment for IR(HOMA-IR) . Metabolic syndrome was defined according to theInternational Diabetes Federation (IDF) 2007 criteria.Results Of92 obese adolescents, IR was found in 38% of subjects,with females predominating (57.2%). Signs of AN were seen in71. 4% of subj ects and a positive family history of metabolic diseaseswas found in 82.8% of subjects, including family history of obesity,type 2 diabetes mellitus (T2DM), and hypertension. Less than10% of subjects were considered to be in a prediabetic state, andnone had T2DM. No statistical significance was found betweengender, family history, or signs of AN and IR (P>0.05). Metabolicsyndromes was found in 19.6% of subjects, with the fo llowingprevalences for each component: 34.8% for hypertension, 78.3%for central obesity, 8.7% for impaired fasting glucose (IFG), 22.8%for low levels of HDL, and 2 1. 7% for high triglyceride levels. Astrong correlation was found between IR and IFG with OR= 5 .69(95%CI 1.079 29.993, P= D.04).Conclusion We find a high prevalence ofIRin obese adolescents,and IR increases the risk of prediabetes. Thus, prevention strategies are needed to overcome the long term impact of obesity on health.